2016
DOI: 10.7874/jao.2016.20.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Maturation of Wave V Latency of Auditory Brainstem Response in Children

Abstract: Background and ObjectivesAuditory brainstem response (ABR) is a noninvasive measurement of a stimulus-locked, synchronous electrical event. ABR provides information concerning the functional integrity of brainstem nuclei. Age is a key factor in the interpretation of ABR peak latency among different age groups. Progressively with time it follows a "maturation pattern" during which latencies decrease. Wave V is very prominent and reliable for detection of threshold in children. The present study was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
(22 reference statements)
2
17
0
2
Order By: Relevance
“…1, critical period). In rodents, the critical period extends from P10 to P14 (de Villers-Sidani et al, 2007) and in humans, it likely occurs between the 27th embryonic week and the sixth to 12th month after birth (Sharma et al, 2016).…”
Section: Tinnitus Occurs With Low Prevalence In Congenital Deafness Bmentioning
confidence: 99%
“…1, critical period). In rodents, the critical period extends from P10 to P14 (de Villers-Sidani et al, 2007) and in humans, it likely occurs between the 27th embryonic week and the sixth to 12th month after birth (Sharma et al, 2016).…”
Section: Tinnitus Occurs With Low Prevalence In Congenital Deafness Bmentioning
confidence: 99%
“…These patients eventually developed hearing loss issues after subsequent additional chemotherapy treatment [41]. Wave V is generated primarily from the inferior colliculus, which is the main midbrain nucleus of the auditory pathway [42,43]. During the first few years of life, wave V latency was found to change regularly where it decreased rapidly in early childhood [43].…”
Section: Discussionmentioning
confidence: 99%
“…Wave V is generated primarily from the inferior colliculus, which is the main midbrain nucleus of the auditory pathway [42,43]. During the first few years of life, wave V latency was found to change regularly where it decreased rapidly in early childhood [43]. This decrease in wave V latency could be attributed to rapid growth in the axonal myelin density in the brainstem pathways and the cochlear nerve during early childhood [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, longer wave latencies were found compared to our research. Because the value of the peak V latency varies among different age person (28). Our study was carried out with adults.…”
Section: Discussionmentioning
confidence: 99%
“…The hearing thresholds specified as dB nHL in ABR is not equal to behavioral thresholds determined as dB HL. As a result, it is suggested to use the correction factor when calculating BHT thresholds (dB HL) from the thresholds (nHL) determined by ABR (25,28). The correction factor, which is used to estimate behavioral hearing thresholds with using of NB CE-Chirp ABR, can be reduced by up to 5 dB (21,16).…”
Section: Discussionmentioning
confidence: 99%